2023
DOI: 10.3390/ijms24119309
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Effect of a Night Shift on Blood Pressure and Clock Gene Expression

Abstract: Night shift work has been found to be associated with a higher risk of cardiovascular and cerebrovascular disease. One of the underlying mechanisms seems to be that shift work promotes hypertension, but results have been variable. This cross-sectional study was carried out in a group of internists with the aim of performing a paired analysis of 24 h blood pressure in the same physicians working a day shift and then a night shift, and a paired analysis of clock gene expression after a night of rest and a night … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Approximately 19–25% of workers in most countries engage in JSW, especially night shifts [ 1 – 3 ]. Such jobs are among the most common external factors underlying disorganised circadian rhythms, which endogenously regulate behavioural and physiological activities over a 24-hour cycle and are crucial for maintaining health [ 4 ].…”
mentioning
confidence: 99%
“…Approximately 19–25% of workers in most countries engage in JSW, especially night shifts [ 1 – 3 ]. Such jobs are among the most common external factors underlying disorganised circadian rhythms, which endogenously regulate behavioural and physiological activities over a 24-hour cycle and are crucial for maintaining health [ 4 ].…”
mentioning
confidence: 99%
“…16 There is substantial evidence that disruptions caused by night-shift work in the circadian system lead to misalignment between the circadian system and the external light-dark cycle, as well as internal desynchronization within the circadian system. 17 Toffoli et al 18 demonstrated that night shifts enhance clock gene expression the following morning, indicative of circadian misalignment, with an independent link observed between night-time blood pressure and Period Circadian Regulator 2-3 (PER2-3) gene expression. Additionally, there is a study that demonstrates the correlation between reverse dipper status and electrocardiographic changes in newly diagnosed hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lower melatonin levels caused by disruption of circadian rhythm may be an important pathway that contributes to the observed associations. Additionally, circadian disruption induced by night shifts can disrupt the normal expression of clock gene expression, such as BMAL, CLOCK, PER1, PER2, and PER3 [46]. The oscillation and dysregulated expression of these clock gene expression have been reported to play a role in COPD pathogenesis, including chronic inflammation and imbalanced autophagy level [47].…”
Section: Discussionmentioning
confidence: 99%